Wednesday

March 4, 2015

March 4, 2015

Posted by **emma** on Saturday, July 11, 2009 at 9:17pm.

- algebra 1 -
**Ms. Sue**, Saturday, July 11, 2009 at 9:29pm14x + 3x - 40 = 11

17x - 40 + 40 = 11 + 40

17x = 51

x = 3

To prove it:

14(3) + 3(3) - 40 = 11

42 + 9 - 40 = 11

51 - 40 = 11

11 = 11

Yep! It works!

**Answer this Question**

**Related Questions**

algebra - solve the following equation by clearing fractions show all work want ...

algebra - solve the following equation by clearing fraction want to know if this...

Equation - Can anyone check this answer for me, simultaneous equation. Where y...

math - which equation is equivalent to 5x-2(7x+1)=14x? why? a -9x-2=14x b -9xt1=...

Maths - find the equation of the perpendicular bisector of the line joining P(2...

Algebra - I have a few questions that I need help with. Solve the radical ...

Algebra2 - The area of a square garden in square feet is 49x^2-14x+1. Find the ...

college algebra - Solve the following equation in the real number system. Please...

math, algebra - this next one i want to make sure that what i'm answering is ...

Algebra 2 help!!! - What value completes the square for the expression? x2 + 14x...